Missing Persons: A Handbook for Parliamentarians (2006)
An introduction to the subject of persons missing or unaccounted for following armed conflict or internal violence, and its impact on the families of the individuals concerned; An explanation of the essential role of parliamentarians in preventing disappearances, elucidating the fate of missing persons and helping their families; A proposal for a model law on missing persons, drawn up by the ICRC’s Advisory Service as a tool to help States and their competent national authorities to adopt legislation designed to prevent, deal with and resolve the type of situations that give rise to disappearances.